Architecture of the MEAN stack : exploring the new web dev tools : MongoDB, ExpressJS, AngularJS, NodeJS (O'Reilly Media, 2015)
"Discover how the MEAN development stack--MongoDB, ExpressJS, AngularJS, NodeJS--changes the architecture and semantics of building a web application. In this incisive video course, you'll learn how NodeJS serves as the MEAN stack platform, ExpressJS acts as the web server, AngularJS delivers the user interface, and MongoDB provides persistence."--Resource description page.